A Simple Optoelectronic Tongue Discriminates Amino Acids. Issue 51 (16th August 2017) - Wang, Benhua; Han, Jinsong; Ma, Chao; Bender, Markus; Seehafer, Kai; Herrmann, Andreas; Bunz, Uwe H. F.
Abstract: A self‐assembled nine‐element optoelectronic tongue consisting of a positively charged water‐soluble poly( para ‐phenyleneethynylene) and three metal ions (Fe 2+, Co 2+, and Cu 2+ ) at three different pH values (7, 10, and 13) discriminates all of the 20 natural amino acids in water. Unknown identification was not ideal. Addition of a highly positively charged green fluorescent protein in the presence of Fe 2+, Co 2+, and Cu 2+ increased the unknown identification to above 86 %. Linear discriminant analysis (LDA) orders the responses according to the amino acid type, that is, hydrophobic, polar, anionic, or cationic. Abstract : Metals make the difference : Self‐assembled optoelectronic tongues consisting of a positively charged water‐soluble poly( para ‐phenyleneethynylene) polymer or a fluorescent protein with a supercharged tag and three metal ions (Fe 2+, Co 2+, and Cu 2+ ) at three different pH values discriminate all of the 20 natural amino acids in water (see scheme).